Negligible Substrate‐Induced Strain Effects on Magnetic Properties of SrRuO3 Thin Films. Issue 8 (4th May 2020) - Lee, Seung Ran; Anwar, Muhammad Shahbaz; Shin, Yeong Jae; Lee, Min-Cheol; Sugimoto, Yusuke; Kunieda, Masanao; Yonezawa, Shingo; Maeno, Yoshiteru; Noh, Tae Won
Abstract : SrRuO3 is known to exhibit strong magnetocrystalline effect, which enables us to control its magnetic properties using lattice engineering. The magnetocrystalline effect of SrRuO3 is systematically investigated under both compressive and tensile strain by depositing SrRuO3 thin films on various oxide substrates with different in‐plane lattice mismatch. All SrRuO3 films have high crystallinity with flat interface and surface. It is found that out‐of‐plane lattice constant is decreased with increasing strain. Moreover, unit cell volume decreases with strain due to structural distortion attributable to RuO6 octahedral distortion as theoretically expected. However, magnetization does not match to any of the theoretical models only considering structural changes; at current stage, internal interactions rather than structural changes seem critical in determining the magnetization of the SrRuO3 films. This study can play a crucial role in understanding internal correlations of magnetic properties in ruthenate films and can trigger research on magnetic functionality. Abstract : High‐crystalline SrRuO3 films are simultaneously grown on different oxide substrates experiencing either compressive or tensile strain. All SrRuO3 films show high quality and their structural change well follows previously proposed theoretical studies under strain. However, magnetization does not match to any of the theoretical models, and at current stage, internal interactions are critical in determining the magnetization of SrRuO3 films.